Management of Avulsed Teeth using Fixed Orthodontics Appliances and Fiber Splint: A Case Series - Wahluyo, Soegeng; Saskianti, Tania; Sudarsono, Wahyudi; Ernestine Harta, Putu Harlia (Indonesian Journal of Dental Medicine, 2018)
Background: Tooth avulsion is defined as the complete displacement of the tooth out of its alveolar socket. The treatment of choice is immediate replantation or if that is not possible, placement of the tooth in an appropriate storage media. Purpose: This paper reported of two cases of treatment management in children who experienced avulsion of the upper central incisor. The first and the second case, discuss about tooth that has been avulsed for 20 hours of unsterilized storage and 4 hours of storage in milk. Case Management: Replantation of those teeth were done by root canal treatment outside the oral cavity first. For the first case followed by splinting method using fixed orthodontics appliances, and for the second case followed by splinting using fiber and composite. Discussion: Evaluation were done every week, until 3 months after replantation to see the the success of the treatment. The progress of two cases with different situation showed good results. Conclusion: The case showed that the tooth that has been avulsed for 20 hours of unsterilized storage and 4 hours of storage in milk could have good prognosis.